Digital jacquard design - Holyoke, Julie (London : Bloomsbury, 2013)
"For centuries, the creation of Jacquard cloth required the collaborative efforts of teams of designers and technicians working on vastly complex equipment. In the past three decades, developments in loom technology and CAD systems have made it possible for a single individual to design and produce this most challenging class of textiles. Digital Jacquard Design presents a comprehensive introduction to the creation of weave patterning in the era of digitally piloted looms. It offers both aesthetic and technical training for students of figured weaving, covering the Jacquard medium in fantastic breadth and depth. The book is an essential guide for all who create figured textiles with modern materials and tools, and provides the reader with a 'digital' key to access and employ the great textile traditions of the past.Digital Jacquard Design examines the design process from end to end, progressing from visual analysis, sample analysis and weave-drafting methods, to figuring techniques and the selection and building of weaves. It provides a guide to converting traditional drafts to digital polychrome format, a design terminology and a weave glossary. The book concludes with a rich set of case studies to demonstrate ingenious and effective weave and design solutions"--
Bibliografische referenties ; index
Keywords: CRAFTS & HOBBIES / Fashion; DESIGN / Textile & Costume; Jacquard weaving; TECHNOLOGY & ENGINEERING / Textiles & Polymers; Textile design; Textile fabrics